1987
DOI: 10.1115/1.3261343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shear Surface Boundaries on Stress for Shearing Flow of Dry Metal Powders—An Experimental Study

Abstract: This paper studies the rapid simple shearing flow of dry cohesionless metal powders contained between parallel rotating plates. In this study, an annular shear cell test apparatus was used; the dry metal powders are rapidly sheared by rotating one of the shear surfaces while the other shear surface remains fixed. Such a flow geometry is of interest to tribologists working in the area of dry or powder lubrication. The shear stress and normal stress on the stationary surface are measured as a function of the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In experiments, a``rough'' boundary is generally used to reduce the slip velocity (Craig, Buckholz andDomoto 1987, Campbell 1993a,b). The above results demonstrate that the roughness angle or the extent of boundary penetration has no signi®cant impact on the roughness of a boundary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments, a``rough'' boundary is generally used to reduce the slip velocity (Craig, Buckholz andDomoto 1987, Campbell 1993a,b). The above results demonstrate that the roughness angle or the extent of boundary penetration has no signi®cant impact on the roughness of a boundary.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, different boundary conditions have been used, either assuming a no-slip condition which mimics a liquid¯ow, or adopting those applying for the viscous liquid¯ows (Schweiwiller and Hutter 1983), or ®nally those based on heuristic arguments (Haff 1983, Hui, Haff, Ungar andJackson 1984). In order to produce a no-slip condition,``rough'' boundaries have been used in which particles are stuck to the boundary walls (Craig, Buckholz and Domoto 1987). These rough boundaries are sometimes termed bumpy boundaries (Jenkins and Richman 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In their results, they reported a scaled solids concentration which accounted for the uncertainty on the location of the boundary of the flow. Craig et al [7] showed that using the same shear cell with top and bottom boundaries made of glued particles resulted in different stresses when different materials were used for the boundary particles. To isolate the boundary geometry effect, type 1 and type 2 results are shown here.…”
Section: Boundary Geometry Effectsmentioning
confidence: 98%
“…This change was made to encourage the extent of shear against settling due to gravity. Craig et al [7] studied the effect of the boundary properties on the flow. It was shown that the stress levels measured are highly influenced by the boundary properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hanes and Inman (1985) performed the experiment by glueing particles on the wall. Craig et al (1987) have also looked at the effect of boundary conditions.…”
Section: Boundary Conditionsmentioning
confidence: 99%